PENGARUH LAMA PENYIMPANAN TERHADAP PERKECAMBAHAN BIJI SAMBILOTO (Andrographis paniculata (Burm.f.) Wallich ex Nees) - Solikin Solikin (BERITA BIOLOGI, 2016)
Sambiloto (Andrographis paniculata (Burm.f.) Wallich ex Nees) belongs to family Acanthaceae is a potential medicinal plant that long traditional (jamu).This research aimed to determine the effect of storage duration on seed germination of sambiloto. The study was conducted in a glass house of Purwodadi Botanic Garden from May 2013 - May 2015. The experiment used completely randomized design with treatments of seed storage duration, namely: S0 = no stored ; S1 = stored for 5 months ; S2 = stored for 9 months ; S3 = stored for 12 months S4 = stored for 18 months and S5 = stored 24 months. The treatments was replicated five times with 100 seeds for each replication. The seeds were sowed on river sand medium sifted with 2 mm sieve mess at about 0.5 cm deep, in polybags (15x10 cm). The polybags were placed in a plastic box 38 x 28 x 13 cm and covered by transparent plastic and black paranet. Variables observed were time, percentage and rate of the seeds germination. The results showed that the seed storage duration had significant effect on the seed germination percentage and rate of sambiloto. The highest seed germination percentage and rate was reached on treatment of 18 months storage duration (S4) with value 91.40 % and 10.72 days respectively. The slowest early seed germination was reached on the treatment S0 (no stored) namely 28,40 days after sowing.